2008
DOI: 10.5664/jcsm.27237
|View full text |Cite
|
Sign up to set email alerts
|

Depression and Sleep-Related Symptoms in an Adult, Indigenous, North American Population

Abstract: S leep disorders are extremely common and have substantial adverse impacts on both quality of life and mental health. Three of the most common sleep disorders are insomnia, obstructive sleep apnea (OSA), and restless legs syndrome (RLS).Psychiatric disorders such as depression and anxiety are more common in people who have insomnia. Furthermore, chronic insomnia is also a risk factor for the development of psychiatric disorders. 1 OSA is a common respiratory sleep disorder characterized by recurrent upper airw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(38 citation statements)
references
References 18 publications
3
34
1
Order By: Relevance
“…Urinary symptoms are common NMSs that cause discomfort and an unpredictable need to use the bathroom at night and may contribute to disrupted sleep. Our findings confirm that depression and anxiety are the main determinants of sleep quality, which is in line with several previous studies that reported that depression was the main determinant of sleep disorders (32)(33)(34)(35). The effects of these symptoms on sleep in PD patients have not been fully examined.…”
Section: Discussionsupporting
confidence: 88%
“…Urinary symptoms are common NMSs that cause discomfort and an unpredictable need to use the bathroom at night and may contribute to disrupted sleep. Our findings confirm that depression and anxiety are the main determinants of sleep quality, which is in line with several previous studies that reported that depression was the main determinant of sleep disorders (32)(33)(34)(35). The effects of these symptoms on sleep in PD patients have not been fully examined.…”
Section: Discussionsupporting
confidence: 88%
“…Some of the studies found higher Epworth Sleepiness Scale (ESS) scores in subjects with RLS, whereas other failed to identify such findings. [12][13][14][15][16][17][18] The aim of this study was to explore the association of EDS with SDB and RLS in acute ischemic stroke. An extensive literature search did not reveal any study on this topic.…”
mentioning
confidence: 99%
“…The British Society of Sexual Medicine Guidelines [8] reports a prevalence ranging from 10 to 52% from several large studies, with a steep age-related increase. ED shares many associated physical conditions with OSA and both have also been demonstrated to affect psychosocial health [4][5][6][8][9][10][11].…”
Section: Journal Of Sleep Disorders and Therapy Review Articlementioning
confidence: 99%
“…It is estimated that the worldwide prevalence is between 9 and 38% [2], however the prevalence in the UK is thought to be just 4% [3]. Patients with OSA have reported increased fatigue, poor quality of life, deterioration of personal relationships, and reduced libido [4][5][6].…”
Section: Introductionmentioning
confidence: 99%